Smartphone Addiction sebagai Pemicu Nyeri De Quervain Syndrome pada Mahasiswa Kesehatan - Faiza, Hani Irfana; Aktifah, Nurul (FORIKES, 2025)
Excessive and uncontrolled smartphone use can lead to addiction, which in turn can lead to de Quervain syndrome pain due to overuse. Individuals who engage in repetitive hand movements can develop de Quervain syndrome pain. The purpose of this study was to analyze the relationship between smartphone addiction and de Quervain syndrome pain in college students. This was a quantitative study with a cross-sectional approach. The subjects were 138 college students selected using a stratified random sampling technique. Both variables were measured by completing the smartphone addiction scale-short version questionnaire for addiction and the numeric rating scale for pain. Data analysis was performed using the Spearman correlation test. The results showed a p-value of 0.003 with a rho of 0.254, indicating a weak positive correlation between smartphone addiction and de Quervain syndrome pain in college students. Therefore, it can be concluded that smartphone addiction is a trigger for de Quervain syndrome pain in college students.Keywords: de Quervain syndrome pain; smartphone addiction; college students ABSTRAK Penggunaan smartphone yang berlebihan dan tidak terkendali dapat menyebabkan adiksi, yang selanjutnya menimbulkan nyeri de quervain syndrome akibat penggunaan berlebih. Individu yang melakukan gerakan tangan secara berulang dapat menyebabkan nyeri de quervain syndrome. Tujuan penelitian ini adalah menganalisis hubungan antara smartphone addiction dengan nyeri de quervain syndrome pada mahasiswa. Penelitian ini merupakan studi kuantitatif dengan pendekatan cross-sectional. Subyek penelitian adalah 138 mahasiswa yang dipilih dengan teknik stratified random sampling. Kedua variabel diukur melalui pengisian kuesioner smartphone addiction scale-short version untuk adiksi dan numeric rating scale untuk nyeri. Analisis data dilakukan dengan uji korelasi Spearman. Hasil analisis menunjukkan nilai p adalah 0,003 dengan rho adalah 0,254, sehingga dapat diinterpretasikan bahwa ada korelasi positif lemah antara smartphone addiction dengan nyeri de quervain syndrome pada mahasiswa. Dengan demikian dapat disimpulkan bahwa smartphone addiction merupakan pemicu nyeri de quervain syndrome pada mahasiswa.Kata kunci: nyeri de quervain syndrome; smartphone addiction; mahasiswa